Scenery Representation in Poetry of the Palestinian Resistance, a Poem "in Jerusalem" by Tamim Barghouthi _an Artistic Approach_ - ا مغربي, محمد رضا (Milev Journal of Research and Studies, 2019)
The Study aims at revealing the features of the scenery representation in the poetry of the Palestinian Resistance. Exactly, the Poem "in Jerusalem" by Tamim Barghouthi. The study starts from the fact that poetry is based on an artistic and dramatic construction which is rich of time, place, music, cinematic, persons and dynamic scenes. All of these are basic components of a scenery representation. By analysing the poem "In Jerusalem" by the young refugee poet Tamim Barghouthi we made a modest attempt to pick up some fruits of the scenery representation between the folds of the vocabulary and the compositions that were embodied in this poem.